(Re-)Narrating the Evolution of the Lancang-Mekong Cooperation: China's Diplomacy Behind the Scenes. Issue 5 (3rd September 2022) - Tungkeunkunt, Kornphanat; Bunyavejchewin, Poowin
Abstract: The launch of the Lancang-Mekong Cooperation (LMC) opened a fresh chapter in international politics in the Mekong region, by marking China's official entry into the continental Southeast Asian arena. However, little is known about the LMC's evolution. By extensively relying on the recently opened Archives in Bangkok, this article illuminates facts and narrates the LMC's formation, with special emphasis on the Chinese perspective. It argues that, similar to Chinese-led regional multilaterals elsewhere, the LMC is a spoke of the continent-wide Belt and Road Initiative (BRI), and functions as a mini-BRI architecture in the Mekong region.